2022
DOI: 10.1080/22423982.2022.2030522
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atrial fibrillation in Greenland: a register-based cross-sectional study based on disease classifications and prescriptions of oral anticoagulants

Abstract: Previous studies of the prevalence of atrial fibrillation (AF) in Greenland are based on either single-point electrocardiograms (ECGs) or patients admitted with stroke. This study estimates the prevalence of AF based on disease classifications in the electronic medical record system (EMR) and prescriptions of oral anticoagulants (OACs). Patients given a diagnose classification code for AF or atrial flutter or prescribed the vitamin K antagonist Warfarin or the direct-acting oral anticoagulant Rivaroxaban were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 39 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…In those age ≥70 years, the prevalence increased to 11.9% (95% CI, 10.3%–13.6%) and 10.1% (95% CI, 8.6%-11.8%), respectively. 50…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…In those age ≥70 years, the prevalence increased to 11.9% (95% CI, 10.3%–13.6%) and 10.1% (95% CI, 8.6%-11.8%), respectively. 50…”
Section: Disorders Of Heart Rhythmmentioning
confidence: 99%
“…Furthermore, data show that the rate of revascularization in Greenlandic citizens is as high as in Danish citizens [ 18 ]. A separate register study investigating the prevalence of AF in Greenland revealed that nearly half of the cases did not have a registered diagnosis of AF/AFL [ 36 ]. Consequently, it is plausible to consider that the actual IR of IHD in Greenland may be higher than our findings suggest, potentially due to a significant number of undiagnosed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of underdiagnosis in Greenland is accumulating. As previously mentioned, the number of unregistered cases of AF/AFL is high, and revascularization rates among Greenlanders are comparable to those of Danes [ 18 , 36 ]. Furthermore, studies indicates that conditions such as osteoporosis and psoriasis are underdiagnosed in the population [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For some conditions/diagnoses, prescription data can be used as a proxy. 34 , 35 Therefore, the Danish National Prescription Registry was also identified as a data source of Diagnosis. Non-clinical outcomes were only used in 12% (n = 25) of the studies with coupling to 17% (n = 12) of the exposure groups and 30% (n = 13) of the registries.…”
Section: Discussionmentioning
confidence: 99%